Risk Factors for Dental Caries in School Children: a Systemic Study - Muhamad Ali (Jurnal Syntax Admiration, 2023)
Caries tooth is multifactorial disease that is most often found in school-age children. Risk factors that need attention are age, gender, fluoride levels, role of parents, eating sweet habits and level of parental knowledge. This systematic study aims to describe the relationship between risk factors and the incidence of dental caries in school children. Search article done through the Garuda Indonesia Portal database, Scholar, Scopus, and Scene Direct and Pubmed in June 2023. The inclusion criteria were research with an observational study design and a focus on the relationship of risk factors (age, sex, fluoride levels, parental roles, eating sweet habits and level of parental knowledge) with dental caries in school children, published between 2018-2023. There are 8 articles reviewed. Risk factors such as age, gender, fluoride levels, role of parents, sweet eating habits and level of parental knowledge have been shown to be associated with an increased risk of dental caries in children. school. Age, type gender, fluoride level , role of parents, habit of eating sweet and level of knowledge of parents increase the risk of dental caries in children.